The Influence of Compensation and Career Development on Employee Retention with Job Satisfaction as Mediation at CV Znepa Karya Mandiri Bekasi - Nursifa, Dea; Rezeki, Fitri; Wulandari, Anna (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
Retaining competent employees is crucial for a company's success, defined as efforts to prevent the departure of talented and potential employees. Employee retention serves as a vital indicator of organizational effectiveness, alongside key factors such as compensation, career development, and job satisfaction. This quantitative study involved a saturated sample of 48 respondents from the total population at CV. Znepa Karya Mandiri. A quantitative approach was used in this research by collecting data through surveys and statistical analysis by, Partial Least Squares analysis was employed using SmartPLS software version 3.2.9. and the results There is a significant positive influence of compensation on employee retention. There is a significant positive influence of career development on employee retention, there is a significant positive influence of job satisfaction on employee retention, there is a significant positive influence of compensation on job satisfaction, there is a significant positive influence of career development on job satisfaction, there is a significant indirect positive influence of compensation on employee retention mediated by job satisfaction, there is a significant indirect positive influence of career development on employee retention mediated by job satisfaction.